Osip Petrov, Anna Petrova-Vorobyova and the Development of Low-Voiced Character Types in Nineteenth-Century Russian Opera. (20th June 2016) - Forshaw, Juliet
Abstract: This article delves into the lives and careers of two significant Russian singers: the bass Osip Petrov and his wife, the mezzo-soprano Anna Vorobyova, who created or inspired leading roles in operas by Glinka, Dargomïzhsky and Musorgsky. Over the course of a career that spanned some four decades, Petrov would become the most celebrated Russian bass of the nineteenth century; Vorobyova, whose career was cut short by a tragic accident, would turn her attention to the private sphere and incubate a younger generation of musicians. Drawing on reviews, memoirs and personal correspondence, I chart the influence of this couple not only on individual composers and operas, but also on the development of stock characters such as the father, the buffoon, the antihero and the trouser role.